Impacts of Food Adulteration and Contamination: Health, Socio-Economic, and Legislative Aspects - Mysha Momtaz; Saniya Yesmin Bubli; Mohidus Samad Khan (Foods, 2026)
Food adulteration is a critical global threat to public health, economic stability, and social welfare. It primarily occurs in two forms: intentional and incidental. Intentional adulteration, or economically motivated adulteration, involves deliberately adding fraudulent or toxic substances such as hazardous ripening agents and harmful coloring to increase profitability. Substitution of food species is also a widely practiced form. Such adulteration can cause severe acute and chronic health issues, ranging from gastrointestinal distress to cancer and organ failure. Incidental adulteration happens through accidental contamination during processing, storage, or distribution, involving hazards such as heavy metals, mycotoxins, and pesticides. Such contaminants also lead to severe chronic diseases and dangerous allergic reactions. Food adulteration also triggers massive socio-economic consequences. Food safety incidents such as the melamine milk crisis and the horsemeat scandal caused billions of dollars in losses due to healthcare costs, product recalls, damaged brand reputation, and disrupted international trade. Global entities such as the WHO, WTO, and Codex Alimentarius have established robust legislative frameworks. However, effective enforcement remains a significant challenge in many countries. To mitigate such harmful impacts, it is essential to strengthen global surveillance systems, enhance rapid analytical detection methods, and strictly enforce compliance with existing food safety regulations.